A review of the application and efficacy of tuina therapy in the treatment of neonatal jaundice (推拿疗法在新生儿黄疸治疗中的应用现状) - YANG Juandong (杨娟东); PANG Lihong (庞立宏); LIU Ling (刘凌); ZHANG Xiaoxia (张小霞); LING Jizu (凌继祖) (中西医结合护理)
Neonatal jaundice is a common condition in the neonatal period, caused mainly by abnormally elevated levels of bilirubin in the body. Tuina therapy, as a traditional Chinese medicine technique, is gradually gaining attention due to its non-invasive nature and potential multiple therapeutic effects. This article reviews the application and clinical effects of tuina therapy in the treatment of neonatal jaundice. The practical application value of Tuina in the management of neonatal jaundice was explored through the analysis of the specific operation, identification and treatment, nursing care and family guidance of Tuina. Meanwhile, Tuina shows unique advantages compared with traditional therapies, and no side effects have been reported, which makes it suitable for implementation in clinical and family environments. (新生儿黄疸是新生儿期常见的疾病, 主要由于体内胆红素水平异常升高而引起。推拿疗法作为一种传统中医技术, 因其非侵入性及潜在的多重治疗效应, 逐渐受到关注。本文综述推拿疗法在新生儿黄疸治疗中的应用现状, 通过对推拿的具体操作、辨证施治、护理与家庭指导进行分析, 探讨其在新生儿黄疸管理中的实际应用价值, 旨在为提升新生儿黄疸的治疗效果和护理质量提供参考。)